Sufis and Sharīʿa The Forgotten School of Mercy - Dajani, Samer (Edinburgh University Press, 2022)
Establishes the existence of an important school of Sufi thought developed by Ibn ʿArabī Gives the first detailed analysis of the legal thought of Ibn ʿArabī, one of the most influential Muslims in general, and Sufis in particularShows that Ibn ʿArabī had created his own madhhab (legal methodology) with a focus on mercy and ease for MuslimsExplores the influence of Ibn ʿArabī, al-Tirmidhī and al-Shaʿrānī on Sufi thoughtIncludes some of al-Shaʿrānī's eight illustrations, his work being the only work of Islamic legal theory that includes drawingsThis book is not about Sufism. It is about the nature of the Sharīʿa. In the first three centuries of Islam, many scholars believed that juristic differences were rooted in the Sharīʿa's inherent flexibility. As this pluralistic attitude began to disappear, a number of Sufis defended and developed this idea through the centuries. They aimed to preserve the leniency and simplicity of the Sharīʿa against the complications and restrictions created by many jurists.This book highlights a number of the major Sufi figures whose writings on legal theory were strongly shaped by their Sufism, showing how they belonged to the same tradition and developed each other's ideas. The book focuses in particular on Ibn ʿArabī, giving a detailed analysis of his legal thought and revealing his influence on a number of major Sufi figures all the way up to the 19th century. Other key figures whose influence is explored are al-Tirmidhī , al-Shaʿrānī and Ibn Idrīs. This is the first study to give a full picture of the role that Sufi thought played in the revivalist Islamic movements of the 18th, 19th and even 20th centuries